2013
DOI: 10.4172/2155-9600.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Evalution of Antioxidant Activity of Various Herbal Folk Medicines

Abstract: The leaves of some plants are flamed and used to dress injured skin, to stimulate healing and to ward off infection. This study aims to determine antioxidant activities of Plantago lanceolata L., Plantago major L. ssp. major, Rubus hirtus Waldst& Kit., Sambucus ebulus L., Morus alba L. and Hedera helix L., which grown in Düzce and its surroundings and are used for anti-inflammatory purposes, and especially for wound-healing. The total phenolic compound of these plants was also evaluated. In order to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay was conducted according to the protocol described by Miser-Salihoglu et al (2013) with some modifications. ABTS radical cation (ABTS·) was produced via reacting ABTS stock solution (7 mM) and potassium persulfate (2.45 mM) for 24 h before the assay.…”
Section: Methodsmentioning
confidence: 99%
“…The 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay was conducted according to the protocol described by Miser-Salihoglu et al (2013) with some modifications. ABTS radical cation (ABTS·) was produced via reacting ABTS stock solution (7 mM) and potassium persulfate (2.45 mM) for 24 h before the assay.…”
Section: Methodsmentioning
confidence: 99%
“…This showed that components which can be extracted from the leaves with polar solvents are more responsible for antioxidant activities. Phenols containing several hydroxyl groups would play an important role for antioxidant activity, since they transfer hydrogen easily to scavenge free radicals and convert themselves into stable phenoxide radicals (Miser-Salihoglu et al, 2013). Therefore, these data indicates that P. lanceolata plant can be used as a good source of antioxidative compounds that control the level of free radical formation in the body.…”
Section: Antioxidant Potential Determinationmentioning
confidence: 92%
“…Plantago lanceolata known by a common name ribwort plantain is one of the species of genus plantago. The Leaves of this plant have been used for traditional medicinal activities in various countries (Miser-Salihoglu et al, 2013;Taskova et al, 2002). In most part of the world including Ethiopia, the plant has not been cultivated on piece of land or large farms since it is considered as weed.…”
Section: Introductionmentioning
confidence: 99%
“…A method based on the description of Miser-Salihoglu E. et al was applied [26]. The examination was performed on a FLUOstar Optima BMG Labtech plate-reader with 96well microplates.…”
Section: Dpph Assaymentioning
confidence: 99%